Navigating Academic Challenges: Self-Regulated Learning Analysis of Academic Procrastination Students - Nurul Fajri; Yuda Syahputra; Sally Putri Karisma; Ifdil Ifdil (KONSELOR, 2023)
The study aims to understand the correlation between self-regulated learning and academic procrastination. By examining responses from 104 students through comprehensive questionnaires, it provides insights into how students manage their learning and delay tasks. The use of simple regression analysis underscores the statistical significance of the findings, highlighting that improving self-regulated learning skills can directly reduce academic procrastination. This research not only contributes to the academic understanding of these concepts but also offers practical guidance for educators and policymakers. By focusing on enhancing self-regulated learning abilities, educational strategies can be developed to address and mitigate procrastination, ultimately improving the overall quality of student learning experiences.